2007
DOI: 10.1523/jneurosci.0651-07.2007
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Ligands for Fish Taste Receptors

Abstract: Recent progress in the molecular biology of taste reception has revealed that in mammals, the heteromeric receptors T1R1/3 and T1R2/3 respond to amino acids and sweeteners, respectively, whereas T2Rs are receptors for bitter tastants. Similar taste receptors have also been characterized in fish, but their ligands have not been identified yet. In the present study, we conducted a series of experiments to identify the fish taste receptor ligands. Facial nerve recordings in zebrafish (Danio rerio) demonstrated th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

18
157
4

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 154 publications
(181 citation statements)
references
References 46 publications
18
157
4
Order By: Relevance
“…2,5) The functional analysis of fish T1Rs and T2Rs was performed using a heterologous expression in cultured cells. 6,7) The mammalian T1R1/T1R3 heteromer detects umami substances (amino acids) and the mammalian T1R2/T1R3 heteromer detects sweet substances. Fish T1R1/T1R3 heteromer-expressing cells responded to some L-amino acids, such as L-Arg and L-Ser in a dose-dependent manner.…”
Section: Identification and Functional Analysis Of Taste Signalingmentioning
confidence: 99%
“…2,5) The functional analysis of fish T1Rs and T2Rs was performed using a heterologous expression in cultured cells. 6,7) The mammalian T1R1/T1R3 heteromer detects umami substances (amino acids) and the mammalian T1R2/T1R3 heteromer detects sweet substances. Fish T1R1/T1R3 heteromer-expressing cells responded to some L-amino acids, such as L-Arg and L-Ser in a dose-dependent manner.…”
Section: Identification and Functional Analysis Of Taste Signalingmentioning
confidence: 99%
“…The fact that the majority of these cells were found in different taste buds, might be related to the species and sets of substances that we used. Ishimaru et al and Oike et al examined the types of taste receptors (T1R and T2R) expressed in the taste buds of zebrafish and medaka (Ishimaru et al, 2005;Oike et al, 2007). They suggested that, among vertebrates, attractive tastants are recognized by T1Rs and aversive tastants by T2Rs.…”
Section: What Type Of Cell Is Stained?mentioning
confidence: 99%
“…Genetic analysis of the fish gustatory system has shown that fish have receptor molecules homologous to those of the mammalian system (8), suggesting that the receptors are conserved as a mechanism through which an organism can distinguish between foods that are nutritious and those that are potentially harmful. Some organisms have other mechanisms for identifying harmful substances, such as the nociceptor pathway; for example, binding of capsaicin (a compound found in chili peppers) to its receptor results in the perception of heat and intense pain in mammals (9).…”
mentioning
confidence: 99%